PENCIPTAAN WANITA - Halimah Basri (Yinyang: Jurnal Studi Islam Gender dan Anak, 2015)
Concerning the creation of woman there are two controversial interpretations. First opinion, the creation of Eve (women)come from the body of Adam (man). Second opinion, the creation of Eve from Adam's creation of a single self or of the same type. Thisopinion offered by contemporary exegetes such as Muhammad Abduh. He explained that the nafs Wahidah is not Adam because thesentence batstsa minhuma rijalan katsiran wa nisaan is in nakirah form. Concerning the hadith, contemporary exegetes understand it in thesense of metaphor, stating that the hadith was warn to the man to deal with the woman wisely because of their innate nature is differentfrom men that if they do not realize will drive him behave inappropriately. Nothing can change that innate nature. Even if there are trying, theconsequences would be fatal, such as efforts to straighten the crooked rib.